Response to letter from Dr Freeman. (March 2015) - Naylor, R.; Knowles, E.; Wilford, S.; Linnenkohl, W.; Taylor, A.; Mair, T.; Johns, I.
<x xml:space="preserve">Abstract</x> See article by Naylor et al. and correspondence by Freeman